Meta-Analysis of Teams Games Tournament Learning Model with Spinning Wheel Media-Based on Local Wisdom Toward Students’ Learning Outcomes - Kurniawati, Devita; Taufiq, Mohammad; Kasiyun, Suharmono; Naufi'ah, Naufi'ah (LPPM Undiksha, 2020)
Research that examines the effect of cooperative learning teams games tournament types on student learning outcomes has been done a lot, but the results of these studies have not received further study to be summarized and tested again the effectiveness of the effect of the learning model used. This study aims to analyze the effect of the use of a team games tournament type cooperative learning model with spinning wheel media-based local wisdom on the learning outcomes of elementary school students. The method used in this research is meta-analysis. The collection of data through online searches using the Google Scholar platform as many as 15 articles were collected with the details of 10 articles representing the learning models of team’s games tournaments and spinning wheel media while the remaining 5 articles are educational articles based on local wisdom. All articles are then analyzed with differences and similarities in data and then reprocessed using SPSS Version 25 using paired sample t-test and showing the Sig. (2-tailed), i.e. (0, 019) <α (0.05). So, H0 is rejected and it can be concluded that there is a significant difference from before and after the use of the learning model that assisted team’s tournament games wheel media in science subjects.